2015
DOI: 10.1177/2325967115599154
|View full text |Cite
|
Sign up to set email alerts
|

SLAP Repairs With Combined Procedures Have Lower Failure Rate Than Isolated Repairs in a Military Population

Abstract: Background:Injuries to the superior glenoid labrum represent a significant cause of shoulder pain among active patients. The physical requirements of military service may contribute to an increased risk of injury. Limited data are available regarding the success of superior labral anterior posterior (SLAP) repairs in an active military population.Purpose:To quantify the rate of clinical failure and surgical revision after isolated and combined SLAP repair.Study Design:Cohort study; Level of evidence, 3.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…It is widely accepted that combined repair of a SLAP lesion and a Bankart lesion produce better clinical outcome than isolated repairs. 2 15 16) Furthermore, in a study by Waterman et al, 17) SLAP repair combined with Bankart repair showed a higher rate of functional return than isolated SLAP repair. Burkart et al 3) reported in their biomechanical study that the repair of type II SLAP lesions only partially restored translations to the same degree of an intact shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that combined repair of a SLAP lesion and a Bankart lesion produce better clinical outcome than isolated repairs. 2 15 16) Furthermore, in a study by Waterman et al, 17) SLAP repair combined with Bankart repair showed a higher rate of functional return than isolated SLAP repair. Burkart et al 3) reported in their biomechanical study that the repair of type II SLAP lesions only partially restored translations to the same degree of an intact shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…Waterman et al reported a failure in 13% (n = 31) of patients with SLAP repair, of whom six patients required revision SLAP repair and 25 patients underwent subpectoral biceps tenodesis. They demonstrated that majority of patients who underwent biceps tenodesis (76%) returned to active duty as compared with those who underwent revision SLAP repair (17%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have demonstrated better results with LHB tenodesis compared with superior labrum repair, 4 , 9 , 14 , 54 , 56 with even worse results for repair in older patients. 54 In spite of this, there is no consensus about a minimum age to decide between labrum repair and LHB tenodesis. In our series, the youngest patient was a 27-year-old male bodybuilder who presented with a superior and anterior labrum lesion.…”
Section: Discussionmentioning
confidence: 99%